Numerical simulation method for water injection-induced fractures in tight oil reservoirs based on PKN model - SHI Dengke; CHENG Shiqing; ZHAO Danfeng; WANG Yang; LIU Xiuwei; XU Zexuan (Youqi dizhi yu caishoulu)
The opening of natural fractures during water injection in fractured tight oil reservoirs can expand the swept volume of water flooding， but it also easily forms high-permeability channels. Therefore， it is crucial to understand the impact of natural fracture opening on water injection development for enhancing the effectiveness of water flooding in tight oil reservoirs. This paper presented a method that coupled the Perkins-Kern-Nordgren （PKN） model with an oil-water two-phase flow model， which utilized the embedded discrete fracture method （EDFM） to establish a numerical simulation approach of oil reservoirs for finely characterizing fracture dynamics during water flooding and compare its results with analytical solutions to verify its accuracy. The numerical simulation results indicate that the fracture propagation velocity at the well bottom exhibits a characteristic of rapid initial expansion followed by a slow-down under constant pressure water injection. The average pressure within the fracture fluctuates due to the opening and closing of fractures during water injection-induced fracture propagation. In a single-injection and single-production mode， there is a critical value for fracture propagation length； the fracture expands the swept volume of water flooding when the fracture propagation length is below the critical value. However， the fracture causes water channeling when the fracture propagation length exceeds the critical value. The proposed coupled model of fracture propagation was applied to numerical simulation studies of unstable water injection in the X low-pressure tight oil reservoir. The results suggest that unstable water injection could moderately induce fracture opening， increase the swept volume of water flooding， prevent rapid water encroachment in oil wells， and significantly improve the water flooding development effect in tight oil reservoirs.